Bioremediation of petroleum hydrocarbons‐contaminated soil by bacterial consortium isolated from an industrial wastewater treatment plant. Issue 7 (18th September 2013) - Gargouri, Boutheina; Karray, Fatma; Mhiri, Najla; Aloui, Fathi; Sayadi, Sami
Abstract BACKGROUND Bioaugmentation is a promising technology to clean up sites contaminated by the petrochemical industry. The paper reports on the bioremediation of a refinery soil containing hydrocarbons in a semi‐arid climate and its impact on the soil microbial community. Two trial plots were established in autumn 2008 to compare two sets of conditions. The first trial is a control (contaminated soil with indigenous microorganismes) and the second is a trial where an acclimatized bacterial consortium was added. RESULTS The proposed bioremediation technology resulted in significantly higher hydrocarbons removal efficiencies than the control. The total amount of petroleum hydrocarbon (TPH) was decreased from 63.4 mg g−1 to 2.5 mg g−1 at the end of the treatment. The treated soil could be considered non‐phytotoxic since the germination index of Lepidium sativum ranged between 80 and 115%. Further, a GC/MS profile proved that the acclimatized bacterial consortium could effectively remove medium‐ and long‐chain alkanes in the contaminated soil after a 30‐day treatment period. Microbial community analysis (16S rRNA and Denaturing Gradient Gel Electrophoresis (DGGE) fingerprints) confirmed the dominance of hydrocarbon degrading genera such as actinobacteria and gamma‐proteobacteria phyla. CONCLUSION These results show that bioaugmentation may be a suitable tool for the remediation of soil contaminated with petroleum hydrocarbons. © 2013 Society of Chemical Industry